A comprehensive characterisation of Laser Sintered Polyamide-12 surfaces. (February 2022) - Nar, Kieran; Majewski, Candice; Lewis, Roger
Abstract: Polymer Laser Sintering (LS) is a powder-based Additive Manufacturing (AM) process known for its ability to produce highly complex geometries. The powder-based nature of the process means it intrinsically produces components with characteristic surface topographies abundant with features, as well as relatively high surface roughnesses, when compared with traditional polymer processing techniques such as Injection Moulding. There are a number of factors which influence the resultant surface topography of LS components and consequently affect their functional performance, particularly when subject to dynamic contact. However, little work has been carried out to date to fully understand these surface determining mechanisms. The scope of this research was to comprehensively characterise the surface topography of LS PA12 specimens and to specifically understand how resultant roughness is a function of applied energy density; XY location across the powder bed; part surface orientation; measurement technique and roughness descriptor. Results showed that the roughness profiles of top and bottom surfaces of cube-shaped samples were distinct in both size and shape. Top surfaces had positive Skewness values and were therefore dominated by asperity peaks, whereas bottom surfaces were neither entirely featureful of peaks nor valleys. Moreover, micro-CT analysis provided insight into how the sub-surface microstructure was affected by part orientation and applied energy density. Resultant binary images revealed the upward-facing section of a cylindrical LS PA12 specimen orientated 45° with respect to the powder bed to be less dense than the downward-facing section of the same sample. This work provides a benchmark for future Polymer Powder Bed Fusion (PBF) studies, specifically when characterising the friction and wear properties of resultant samples. Highlights: Top and bottom surfaces of Laser Sintered PA12 components are distinct in size and shape. Top surfaces of Laser Sintered PA12 components are dominated by asperity peaks. Bottom surfaces of Laser Sintered PA12 components are neither entirely featureful of peaks nor valleys. Sub-surface porosity is affected by part orientation and applied energy density.